On Equations of Lund-Regge Type - Reyes-Garcia, E; Benson-Radrigan, A (Academic Press, 2025)
We introduce a new class of partial differential equations admitting a geometric interpretation, the class of equations of Lund-Regge type. These equations describe surfaces immersed in a three dimensional euclidean sphere, admit conservation laws, and they are the integrability condition of 3×3 overdetermined so(3,R)-valued linear systems. As examples, we present equations describing minimal surfaces, equations describing spherical surfaces, a generalization of the integrable Konno-Oono coupled system, and an elliptic Lund-Regge equation that generalizes the sinh-Poisson equation of plasma physics. We also present a structural result on second order equations of Lund-Regge type. © 2025 Elsevier Inc.